Madness, Insanity and Despair in Quiroga - Pulido, Alexander Vivero (Advances in Social Sciences Research Journal, 2023)
This paper evidences the intrinsic relationship between five stories of Quiroga´s collection Cuentos (Quiroga, 2017) and the reflection of madness, insanity and despair related to his life. The humanity and depth of his characters and his bond with nature are also briefly discussed, along with the emotional whirlwind of its figures. The tragic ending described in El almohadón de plumas and the derangement in La gallina degollada make it possible to observe the clear influence of the writer’s life in his work and the constant presence of feelings portrayed in a motley way. The descriptions and environments displayed by the author, precise and naive at all times, allow the reader to create fairly clear and constant depictions of the scenarios that take place in the text. Furthermore, having experienced such profound feelings firsthand allows the author to express tragedy in his texts in such a way that it resonates with the readers. All of the abovementioned factors, among many others, make Horacio Quiroga one of the Spanish language greatest writers.